Strategies for growth in SMEs : the role of information and information systems. - Levy, Margi, ....-; Powell, Philip, ....- (Amsterdam : Elsevier, Butterworth and Heinemann, 2005)
1 Introduction 2 Background to SMEs 3 Information and IS in SMEs 4 Flexibility in IS 5 Evaluating IS in SMEs 6 Understanding IS strategy in SMEs 7 An organizational approach to IS strategy 8 Case example of ISS : Heath Springs 9 Strategic context of IS investment 10 Strategic IS dynamics 11 Exploring business transformation through IS 12 Strategic alignment 13 IS role in co-opetition and knowledge sharing 14 Role of core competencies in developing ISS in knowledge-based SMEs 15 Exploring business process re-engineering in SMEs 16 Exploring e-business in SMEs 17 Strategic intent and e-business 18 E-business influencers 19 Managing IS : the future
Keywords: Informatiesystemen; Ondernemingen